Pengaruh Pertumbuhan Ekonomi, Indeks Pembangunan Manusia, dan Tingkat Pengangguran Terbuka terhadap Tingkat Kemiskinan di Provinsi Jambi - Reki Ardian; Yulmardi Yulmardi; Adi Bhakti (Jurnal Ekonomi Aktual, 2021)
This study aims to determine the development and influence of economic growth, Human Development Index, open unemployment rate, and poverty level in Jambi Province. The study is a descriptive and quantitative analysis using time series data from 2000 to 2017. The study results show that during the period 2000-2017, economic growth and Human Development Index significantly affected the poverty level in Jambi Province. Meanwhile, the open unemployment rate had no significant effect on the poverty level in Jambi Province.